Angiogenesis and neuronal remodeling after ischemic stroke - Hatakeyama, Masahiro; Ninomiya, Itaru; Kanazawa, Masato (Neural regeneration research, 2020)
Increased microvessel density in the peri-infarct region has been reported and has been correlated with longer survival times in ischemic stroke patients and has improved outcomes in ischemic animal models.This raises the possibility that enhancement of angiogenesis is one of the strategies to facilitate functional recovery after ischemic stroke. Blood vessels and neuronal cells communicate with each other using various mediators and contribute to the pathophysiology of cerebral ischemia as a unit. In this mini-review, we discuss how angiogenesis might couple with axonal outgrowth/neurogenesis and work for functional recovery after cerebral ischemia. Angiogenesis occurs within 4 to 7 days after cerebral ischemia in the border of the ischemic core and periphery. Post-ischemic angiogenesis may contribute to neuronal remodeling in at least two ways and is thought to contribute to functional recovery. First, new blood vessels that are formed after ischemia are thought to have a role in the guidance of sprouting axons by vascular endothelial growth factor and laminin/β1-integrin signaling. Second, blood vessels are thought to enhance neurogenesis in three stages: 1) Blood vessels enhance proliferation of neural stem/progenitor cells by expression of several extracellular signals, 2) microvessels support the migration of neural stem/progenitor cells toward the peri-infarct region by supplying oxygen, nutrients, and soluble factors as well as serving as a scaffold for migration, and 3) oxygenation induced by angiogenesis in the ischemic core is thought to facilitate the differentiation of migrated neural stem/progenitor cells into mature neurons. Thus, the regions of angiogenesis and surrounding tissue may be coupled, representing novel treatment targets.